Why so Few, Still? Challenges to Attracting, Advancing, and Keeping Women Faculty of Color in Academia - Fox Tree, Jean E.; Vaid, Jyotsna (Frontiers in Sociology, 2022)
From its earliest beginnings, the university was not designed for women, and certainly not for women of color. Women of color in the U.S. are disproportionately under-represented in academia and are conspicuous by their absence across disciplines at senior ranks, particularly at research-intensive universities. This absence has an epistemic impact and affects future generations of scholars who do not see themselves represented in the academy. What are the barriers to attracting, advancing, and retaining women faculty of color in academia? To address this question we identify disparities that arise in the assessment of research, teaching, and service that in turn affect hiring, tenure, and retention processes. These disparities have distinct implications for the hiring, promotion, and professional visibility of women of color. We conclude by suggesting some interventions. These include acknowledging and validating the experiences of women faculty of color, using assessment techniques that decrease bias, supporting and valuing research by women of color, creating opportunities for their professional recognition and advancement, and implementing corrective action for unjust practices.